Vector control of an open-ended winding induction machine based on a two-output indirect matrix converter - Riedemann, Javier; Clare, Jon C.; Wheeler, Patrick; Blasco Giménez, Ramón; Cardenas, Roberto; Pena, Ruben (European Power Electronics and Drives Association, 2017)
The open-ended winding induction machine fed from a standard two-level Voltage Source Inverter (VSI) arrangement is an attractive solution for AC drives. An alternative power converter approach is to use an Indirect Matrix Converter (IMC) consisting of a matrix converter AC-DC input stage and two VSI output stages. This latter topology provides fully bidirectional power flow operation and requires only a small input filter. In this paper, a vector control strategy for an open-ended winding cage induction machine fed by a two-output IMC is presented. The modulation scheme for the input power converter stage aims to modify the virtual DC link voltage depending on the load voltage requirement. Additionally, the modulation strategy for the dual-inverter output aims to eliminate the zero sequence voltage applied to the load. A vector control scheme is used and the full system is modelled using a PSIM and MATLAB/Simulink platform. Experimental results from a 7.5 kW prototype are presented, demonstrating the feasibility of the topology and control strategy.